Pengaruh Model RADEC Berbantuan Canva terhadap Kemampuan Berpikir Kritis Siswa kelas IV - Nurghozali, Deka; Maufur, Syibli; Setiawan, Dadan (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2025)
This study aims to evaluate the effect of the RADEC learning model assisted by Canva on the critical thinking skills of fourth-grade students at MI Salafiyah in Indonesian language learning. The research was motivated by the low critical thinking ability of students due to conventional teaching methods that lacked active student engagement. A quasi-experimental approach with a nonequivalent control group design was employed. The sample consisted of 44 students: 23 in the experimental class and 21 in the control class. A critical thinking essay test was used as the instrument, administered before and after the treatment. The results showed that the average score of the experimental group increased from 41.96 to 75.65 (an increase of 80.1%), while the control group improved from 43.33 to 59.76 (an increase of 38%). An Independent Sample T-Test yielded a significance value of < 0.001, indicating a significant difference between the two groups. It can be concluded that the RADEC model assisted by Canva is effective in improving students’ critical thinking skills.